2015
DOI: 10.7812/tpp/14-085
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Neck Hematoma after Thyroid or Parathyroid Surgery: Ten-Year Analysis of the Nationwide Inpatient Sample Database

Abstract: We identified demographic and clinical factors associated with increased risk of neck hematoma after thyroid or parathyroid surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 39 publications
3
32
2
1
Order By: Relevance
“…8,9 While patient comorbidities or the extent of surgery required may make outpatient surgery a less viable option for some, specific data regarding risk factors for POH are sparse. 10,11 If concern for POH is the main reason for avoidance of same-day surgery, better data are needed to help clarify which patients may in fact be high risk for POH and thus justify observation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 While patient comorbidities or the extent of surgery required may make outpatient surgery a less viable option for some, specific data regarding risk factors for POH are sparse. 10,11 If concern for POH is the main reason for avoidance of same-day surgery, better data are needed to help clarify which patients may in fact be high risk for POH and thus justify observation.…”
mentioning
confidence: 99%
“…While the risk of continued therapy has been explored in other surgical specialties, the impact during thyroid and parathyroid procedures is unknown. 11,1419 …”
mentioning
confidence: 99%
“…A large multi-institutional international study conducted on over 200 hematomas showed that this complication is associated with the use of a drain, or Graves' disease, antiplatelet/anticoagulation medications and large goiters. Moreover, the Authors affirm that a residual thyroid parenchima, that can be found after hemithyroidectomy or subtotal thyroidectomy, can increase the risk of bleeding (42,43). These findings could lead to a more accurate selection of patients proposed for short stay surgery.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 95%
“…Although the incidence of the definitive hypoparathyroidism decreases respectively to 6,1% and 11,9% for the first-time and the "redo" surgery ones, these values should be considered on the whole high and it should worry in case of early discharge (9). As the hypocalcaemia is the most common morbidity associated with thyroid surgery, it should be the more prominent reason for the decision concerning the time of the discharge, but even the compressive hematoma, although rare, plays an important role in this decisionmaking, since it is a life threatening complication (12,13). Moreover, the inferior laryngeal nerve palsy causes respiratory compromise only if bilateral (8,9,14).…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors for PCH have been described in the literature such as advanced age, male gender, smokers, presence of chronic diseases, anticoagulant or antiaggregant therapy, significant resections or reinterventions substernal thyroidectomy, large dominant nodule, inflammatory thyroid diseases, thyrotoxicosis, use of drains, lymph node dissection, parathyroidectomy, [6,[10][11][12]. According to literature, surgeon's experience is also of great value, and rates between 2% and 14% were reported [4], whereas others reported up to the sevenfold difference between individual surgeons [8].…”
Section: -33mentioning
confidence: 99%